Improving Students’ Sustainability Awareness through Argument-driven Inquiry - Erning Rahmadini Salsabila; Agus Fany Chandra Wijaya; Nanang Winarno (Journal of Science Learning, 2019)
Sustainability awareness is one of the things that the student should have to help in a caring environment. Sustainability awareness of the student can be built by knowledge and awareness of what should be done or not. The student will be more aware of the students involved and explore more in building a concept about the environmental issue itself. The aim of this study is to investigate the impact of Argument-Driven Inquiry toward students' sustainability awareness in learning global warming. The method used in this research was experimental research. This study used two different groups of student. The first group learned using Argument-Driven Inquiry and the second group learned using Inquiry-based Learning. The population was seventh-grade students in one of Junior Secondary School in Bandung, Indonesia. The purposive sampling technique was used to choose the sample. The participants consist of 52 students from both groups. Each group consists of 26 students. The data were collected by giving the questionnaire of sustainability awareness. The questionnaire consists of 15 items. The result of this study shows the different percentage in the level of students' sustainability awareness between the two groups. The most different percentage is on the sustainability practice awareness aspect. The group that used Argument-Driven Inquiry has percentage 40.7% which means as medium and the group that used Inquiry-based Learning has percentage 37.6% which means as low. Based on the result, Argument-Driven Inquiry gives a better impact on students’ sustainability awareness. Argument-Driven Inquiry can be considered as one of the alternative teaching models that can give a better understanding in building the awareness of Junior Secondary School student.